SYSTEMATIC LITERATURE REVIEW: ANALISIS IMPLEMENTASI ENTERPRISE RESOURCE PLANNING (ERP) TERHADAP KINERJA PERUSAHAAN - Intani, Fitria -; Razak, Muh. Fajar Alamsyah; Indrajawati, Aini; Ferdiansah, Muhammad Irdam (Jurnal Akuntansi Sektor Publik, 2023)
The era of globalization, which was followed by the rapid development of technology, has encouraged an increase in the number and type of companies of the same type of business. Therefore, we need a system that can facilitate the company's operations in the context of the effectiveness and efficiency of the company's performance. This study aims to find out how the situation and development of ERP implementation within the company. The research method used is a systematic literature review. The samples used were 30 articles. The results of the study explain that the problems regarding ERP technology with ERP implementation costs are very expensive, then the ability of resources to run ERP so that the system runs well and also each company should identify what module is suitable for their company. In the 2011-2022 year, the most studied ERP implementation was in 2021 with the most frequently used research methods, namely quantitative methods and qualitative methods.